Are fear of missing out and loneliness a symptom of narcissistic behaviour? - Imelda Pristaliona; Diana Savitri HIdayati; Susanti Prasetyaningrum (Cognicia, 2022)
Adolescence is known as a period of self discovery. Adolescents who can find their identity will feel more meaningful when they can connect with their social environment. However, when a teenager cannot find his identity, he will tend to withdraw from the social environment and experience a loneliness. This study aims to determine how much fear of missing out (fomo) and loneliness can have influence on the narcissistic behavior of adolescent Instagram users. The number of respondents used in this study were 164 teenagers are active users of social media Instagram. The sampling technique in this study used incidental sampling by using research instruments in the form likert scale about a narcissistic behavior scale, a fear of missing out scale, and a loneliness scale. The data analysis technique used is in the form of multiple regression analysis. The results showed that the significance value of the F test was 0.000 (p < 0.05). It can be seen that fomo and loneliness can simultaneously influence adolescents to behave narcissistically by 55.3%. Keywords: Fear of missing out, instagram, loneliness, narcissistic behavior, teenagers